Lack of lipolytic response in infants after endotracheal intubation. Issue 3 (March 1993) - Marcus, C; Selldén, H; Rickardsson, E; Lönnqvist, P A; Brönnegård, M; Arner, P
Abstract : The sympathoadrenal response to endotracheal intubation was investigated in nine infants 2-4 months old and in eight adults 23-45 years old at the start of inguinal hernia operations. In both infants and adults, heart rate and diastolic blood pressure increased significantly immediately after intubation. In both groups, moreover, there was a mean (SD) reduction in microvascular blood flow in the abdominal skin (infants -21 (14)%, adults -14 (7)%) and in the adipose tissue (infants -7 (4)%, adults -5 (4)%). However, the plasma glycerol concentration did not increase in the infants whereas it increased in the adults by 50 (12)%. In conclusion, infants and adults showed similar circulatory reactions during endotracheal intubation but the markedly increased lipolysis rate observed in adults was not seen in the infants. This may indicate that catecholamine induced lipolysis in vivo as well as in vitro is poor during infancy.